2009
DOI: 10.1177/0091270008331133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Durations of Ketoconazole Dosing on the Single‐Dose Pharmacokinetics of Midazolam: Shortening the Paradigm

Abstract: Given the prominent role of cytochrome P450 3A (CYP3A) in the metabolism of drugs, it is critical to determine whether new chemical entities will be affected by the inhibition of this enzyme system and result in clinically relevant drug interactions. Ketoconazole interaction studies are frequently performed to determine a given compound's sensitivity to CYP3A metabolism. The present study evaluated whether probing a sensitive substrate (midazolam) with a potent inhibitor (ketoconazole) at earlier time points (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 20 publications
(30 reference statements)
7
48
0
Order By: Relevance
“…For example, a 36% higher midazolam AUC was observed after 5 days of ketoconazole (400 mg QD) treatment, relative to a single dose (Stoch et al, 2009). This time dependence provides an unusual challenge for DDI predictions, because ketoconazole does not accumulate in plasma after multiple doses, and data obtained from human liver microsomes are generally characterized as rapidly reversible and competitive in nature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a 36% higher midazolam AUC was observed after 5 days of ketoconazole (400 mg QD) treatment, relative to a single dose (Stoch et al, 2009). This time dependence provides an unusual challenge for DDI predictions, because ketoconazole does not accumulate in plasma after multiple doses, and data obtained from human liver microsomes are generally characterized as rapidly reversible and competitive in nature.…”
Section: Discussionmentioning
confidence: 99%
“…A complete search of the literature using the Metabolism and Transport Drug Interaction Database (University of Washington, Seattle, WA) indentified 11 clinical DDI studies and 16 dosage scenarios from 17 published clinical results using midazolam as CYP3A probe (intravenous and oral) and ketoconazole as inhibitor (400 mg QD and 200 mg QD and BID for various durations) as of 2012 (Olkkola et al, 1994;McCrea et al, 1999;Tsunoda et al, 1999;Goh et al, 2002;Lee et al, 2002;Lam et al, 2003;Eap et al, 2004;Chung et al, 2006;Tham et al, 2006;Yong et al, 2008;Krishna et al, 2009;Stoch et al, 2009). The specific treatment regimens of ketoconazole and midazolam used in the literature reports were reproduced in the simulations.…”
Section: Model Validation and Simulationmentioning
confidence: 99%
“…The intended sample size was based on the known variability in the AUC and C max associated with midazolam. Sample size calculations were based on a study by Stoch et al (11), who reported 90% CIs for GMRs of midazolam AUCs based on within-subject AUC variability and midazolam 2-mg oral doses in the presence of ketoconazole. The natural log-scale standard deviations (SD) computed from these CIs were 0.22 for AUC and 0.31 for C max .…”
Section: Methodsmentioning
confidence: 99%
“…On day 5, either 30 mg tolvaptan or placebo was co-administered with the ketoconazole. Previously it was determined that 1 day of pre-exposure to ketoconazole was sufficient to produce a maximal inhibition of midazolam pharmacokinetics [10]. Ketoconazole dosing was continued on day 6 to ensure inhibition was sustained through out the tolvaptan washout period.…”
Section: Trial Designsmentioning
confidence: 99%